Rendering performance comparison of react, vue, next, and nuxt - Mangapul Siahaan; Ryan Kenidy (Jurnal Mantik, 2023)
This article presents a comprehensive analysis of the rendering performance of four popular JavaScript frameworks: React, Vue, Next.js, and Nuxt.js. In an increasingly competitive web development landscape, performance optimization is paramount. By exploring various benchmarks, profiling tools, and real-world use cases, this study delves into how these frameworks handle rendering, component updates, and server-side rendering (SSR). The results offer developers valuable insights into choosing the most suitable framework for their projects, with a focus on delivering optimal user experiences and efficient web applications. The results conducted with WebPageTest, PageSpeedInsight, and GTMetrix show that Vue is the fastest in the average result tested with Webpage Test with 0.9s compared to Nuxt with 2.2s. For PageSpeed Insight, React outperforms other frameworks with 2.8s compared to the highest which is Next with 3.9s. In GTMetrix test, Next turns out to be the fastest framework with 0.8s, while React is the slowest with 1.4s